EVALUATION OF ACID LIME (CITRUS AURANTIFOLIA) VARIETIES IN LATERITIC SOIL CONDITIONS OF ANDHRA PRADESH - D, NAGARJUNA (The Journal of Research ANGRAU, 2026)
The present study was undertaken at Agricultural Research Station, Kavali during 2022 2024 to assess the performance of three acid lime cultivars, namely Pramalini, Balaji and Petluru Selection 1 under red lateritic soil conditions. The experimental layout followed a Randomized Block Design comprising seven replications for comparative evaluation. Among the tested cultivars, Petluru Selection 1 recorded superior growth (plant height 4.47 m; plant spread 4.18 m), yield (414 fruits/plant; 15.71 kg/plant) and juice content (55.3%), along with higher consumer preference, indicating its suitability for lateritic soils of Andhra Pradesh.